Interpretation of Media System Dependency Theory on Financial Technology - Nurliya Ni'matul Rohmah; Endang Rahmawati (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2023)
A study on the interpretation of people's dependency behavior on digital technology, one of which is in the financial sector in daily life by adapting the theory of Media Dependency System. This article discusses the application of the theory which consists of (1) an analysis of dependence on fintech based on the social system of womenprenuers in Lombok; and (2) interpretation of media system dependency theory on fintech. A total of 108 samples from the population of womenprenuers in Lombok to test its statistical hypotheses. The results revealed there is a positive correlation between the location of the respondents, the business they were in and the financial platform used simultaneously on their dependence on fintech ecosystem